The nature of the rules on contract interpretation - Forno Flórez, Hugo (2024)
Contract interpretation clauses are tools granted by the Civil Code. The discussion on the character they have (they could be mandatory or simple suggestions) has been a long doctrinal and even legislative debate. The author, by means of a historical and theoretical review of this institution around the world, but especially of the European legislations –which are the influence of ours–pronounces on the matter and argues that there is, in fact, a duality in the nature of these rules, since these categories, in the context they have been used, would not be mutually exclusive.The importance of understanding these rules in this way lies in the fact that this is the only way to achieve a balance between legal certainty and contractual freedom.